Comparisons of efficiencies between two types of DMUs : an application to Japanese public water companies - Takuya Urakami; Noriyoshi Nakayama (European Regional Science Association (ERSA), 2003)
A water supply system composed of water production facilities and transmission facilities obtains water from various sources such as surface water, groundwater and so on. Although there are many empirical studies such as measuring efficiency, productivity and/or returns to scale for water supply organizations, almost all of them neglect the variety of water sources. The main purpose of this study is to compare the efficiencies of two types of DMUs (decision making units) e.g. water companies whose major source is underground vs. those whose major source is non-underground. In this study, using observations of Japanese public water companies, we will apply rank-sum-test of DEA (data envelopment analysis) approach developed by Wilcoxon-Mann-Whitney to identify whether the differences between two gropes are significant. After we examine whether two groups of DMUs have different distribution functions of efficiency, we will measure efficiencies of two gropes and compare them.
Keywords: 330